Allosteric Control of Ligand Binding Affinity Using Engineered Conformation-Specific Effector Proteins - Rizk, Shahir S. (2011)
We describe a phage display methodology to engineer synthetic antigen binders (sABs) that recognize either the apo- or the ligand-bound conformation of maltose binding protein (MBP). sABs that preferentially recognize the maltose-bound form of MBP act as positive allosteric effectors by significantly increasing the affinity for maltose. A crystal structure of a sAB bound to the closed form of MBP reveals the basis for the exhibited allosteric effect. We show that sABs which recognize the bound form of MBP can rescue the function of a binding-deficient mutant by restoring its natural affinity for maltose. Further, the sABs can enhance maltose binding in vivo by providing a growth advantage to bacteria under low maltose conditions. The results demonstrate that structure-specific sABs can be engineered to dynamically control ligand-binding affinities by modulating the transition between different conformations.